PERANCANGAN DAN PEMBANGUNAN APLIKASI INFORMASI ABSENSI DENGAN WHATSAPP NOTIFIKASI KEPADA WALI MURID DI SMK SULTAN AGUNG MENGGUNAKAN MODEL WATERFALL - Muhamad Ridwan Wijaya; Ines Heidiani Ikasari (Journal of Research and Publication Innovation, 2025)
Student attendance at school or other educational institutions is a key indicator in evaluating learning regularity and discipline. Absenteeism without a clear reason and lack of communication between schools and guardians make it difficult for guardians to monitor the attendance of their children in real time. The main objective of this research is to design a student attendance application that is safe, efficient, and can facilitate the work of teachers in inputting attendance data. In addition, this research also aims to develop a WhatsApp notification feature that allows schools to provide instant information to student guardians regarding student attendance. The methodology used in developing this application is the Waterfall method, which consists of the stages of requirements (needs analysis), system design, coding and testing, program implementation, and maintenance. This approach was chosen to ensure systematic and structured development. The results showed that the new attendance system was successfully designed and implemented using MySQL database, significantly improving security and efficiency compared to the previous manual system. This system successfully overcomes data security issues and increases the efficiency of attendance input by teachers. In addition, the integration with WhatsApp as a notification tool has improved the speed and effectiveness of delivering student attendance information to student guardians, especially in cases of permission, illness, or unexplained absence. The implementation of this application has successfully improved the effectiveness of student attendance management and facilitated communication between the school and student guardians at SMK Sultan Agung.